The hidden foundation : cinema and the question of class - James, David E., 1945-; Berg, Rick (University of Minnesota Press, 1996)
Ranging from the earliest days of the cinema to the present, The Hidden Foundation reestablishes class as a fundamental aspect of film history. Featuring prominent film scholars and historians acting to inaugurate a new type of film studies, this volume is unique in its international scope, diversity of perspectives and methodologies, and the cultural, political, and historical sweep of its analysis.